Assessment of the impact of pharmacy learners on admission medication reconciliation in Toronto, Canada. (12th October 2020) - Chow, Matthew; Lui, Philip; Cameron, Karen; Romanko, Anatoliy; Hamandi, Bassem; Gorman, Sean; Harrison, Jennifer; Murphy, Laura; Cameron, Andrea; Toombs, Kent; Meade, Andrea; Wong, Gary; et al.
Abstract: Introduction: Currently there is a lack of published data examining the clinical impact of pharmacy learners on patient care outcomes in acute care. A collaborative of hospital pharmacists in Canada established consensus on eight clinical pharmacy key performance indicators (cpKPIs) representing essential patient processes of care. Of the eight cpKPIs, admission medication reconciliation has been established as a cornerstone patient care process. The implementation of cpKPI measurement creates an opportunity to quantify pharmacy learner contribution to patient care. Aim: To determine if the presence of pharmacy learners partnering with pharmacists is associated with an increased number of patients receiving admission medication reconciliation (AMR). Methods: In this prospective observational study, pharmacists and learners (on 5‐week rotations) tracked patients receiving AMR in the electronic health record from 25 January to 17 July 2016. The number of patients receiving AMR were compared during timeframes when a learner was present (intervention) to when a learner was not present (control). Results: In the main analysis of 30 learner‐pharmacist pairs with 4684 patients, 1136 patients received AMR in the intervention group versus 887 patients in the control group (adjusted for 5 weeks). The number of patients receiving AMR in the presence of a pharmacy learner partnered with a pharmacist (median = 43, IQR = 23–59) was significantly increased compared to the presence of a pharmacist alone (median = 36, IQR = 17–53, p < 0.001). Learners partnered with pharmacists to perform AMR for 41% of the patients. Conclusion: Overall, pharmacy learners partnering with pharmacists increased the number of patients receiving AMR.